(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study delves into the comparative performance of ‘public and private insurance companies’ in the dynamic Indian market, focusing on Return on Asset (RoA), Claim Settlement efficiency, and Risk Management practices. The overarching goal is to provide nuanced insights into the operational disparities between the two sectors and offer strategic recommendations for industry stakeholders. The research methodology involves selecting representative samples of 10 Indian Public and 10 Indian Private insurance companies based on market prominence and data availability. Financial metrics, including RoA, Claim Settlement, and Risk Management data, are compiled from reliable sources like IRDAI Annual Reports and financial databases for the fiscal year 2021-22. Descriptive statistics, t-tests, and MS-Excel are employed for data analysis. Results reveal significant differences in performance metrics. Private insurers exhibit higher RoA and superior Claim Settlement efficiency compared to public insurers. Additionally, private insurers demonstrate a greater effectiveness in Risk Management practices. The study underscores the influence of ownership structure on operational efficiency and risk mitigation approaches in the Indian insurance sector. The findings have implications for industry stakeholders, regulators, and policymakers Recommendations emerge from the findings as public insurers could enhance risk management practices, aligning them with private counterparts, and explore avenues for process optimization to narrow performance gaps. For private insurers, maintaining their competitive edge requires a continued focus on innovation and customer-centric approaches. Policymakers may find the insights valuable for refining regulatory frameworks to foster healthy competition and innovation.